Effects of Different Infra-Red Irradiations on the Survival of Granary Weevil Sitophilus granarius: Bioefficacy and Sustainability - Sándor Keszthelyi; Helga Lukács; Ferenc Pál-Fám (Insects, 2021)
Sitophilus granarius (L.) is an important pest of stored grain worldwide. In recent years, sustainable methods against it have received attention as grain stock protective means. Our aim was to obtain information about the efficacy of infrared irradiation (IR) against S. granarius in laboratory conditions. The change in adult-activity and median lethal dose (LD50) triggered by IR in S. granarius was examined. The insecticidal efficacy in the infested grains was also analyzed at 12, 24, 48, and 72h following exposure to IR (250W), and the progeny-production was assessed 45 days upon the treatment. Based on our findings, total mortality ensued in a grain stock of 50 g at 412 s and a for 100 g grain at 256 s. A significant increase in S. granarius mortality could be observed in the higher grain weight regime, which can be accounted for by the higher heat-absorbance of objects with higher weight. The activity of pests immediately after the beginning of IR increased and subsequently became moderated. The observation of activity-peak brought about by irradiation contribute to the optimization of chemical intervention. This treatment could provide an effective and sustainable technique in integrated pest management.